World Trade Center-related physical and mental health burden among New York City Fire Department emergency medical service workers. Issue 1 (15th April 2015) - Yip, Jennifer; Zeig-Owens, Rachel; Webber, Mayris P; Kablanian, Andrea; Hall, Charles B; Vossbrinck, Madeline; Liu, Xiaoxue; Weakley, Jessica; Schwartz, Theresa; Kelly, Kerry J; Prezant, David J
Abstract : Objectives: To describe the health burden among Fire Department of the City of New York (FDNY) emergency medical service (EMS) workers and examine its association with work at the World Trade Center (WTC) disaster site. Methods: In this observational cohort study, we used FDNY physician diagnoses to estimate the cumulative incidence of physical health conditions including rhinosinusitis, gastroesophageal reflux disease (GERD), obstructive airways disease (OAD) and cancer among EMS workers and demographically similar firefighters who were active on 11 September 2001 (9/11). Validated screening instruments were used to estimate the prevalence of probable post-traumatic stress disorder (PTSD), probable depression and probable harmful alcohol use. We also analysed the association between health conditions and WTC-exposure. Results: Among 2281 EMS workers, the 12-year post-9/11 cumulative incidence (11 September 2001 to 31 December 2013) of rhinosinusitis was 10.6%; GERD 12.1%; OAD 11.8%; cancer 3.1%. The prevalence of probable PTSD up to 12 years after exposure was 7%; probable depression 16.7%; and probable harmful alcohol use 3%. Compared with unexposed, EMS workers who arrived earliest at the site had higher adjusted relative risks (aRR) for most conditions, including rhinosinusitis (aRR=3.7; 95% CI 2.2 to 6.0); GERD (aRR=3.8; 95% CI 2.4 to 6.1); OAD (aRR=2.4: 95% CI 1.7 to 3.6); probable PTSD (aRR=7.0; 95% CI 3.6 to 13.5); and, probable depression (aRR=2.3; 95% CI 1.6 to 3.1). Conclusions: In this 12-year study, we documented a high burden of health conditions associated with WTC-exposure among FDNY EMS workers. These findings underscore the importance of continued monitoring and treatment of this workforce.